“The wandering poet”; Depictions on ancient Javanese relief panels - Kieven, Lydia (UI Scholars Hub, 2022)
A bstract There are about 60 panels with narrative reliefs from the area of Trowulan in East Java depicting mountains, rivers, bridges, trees, fields, dwellings, pendopo, and palaces. A male figure wearing a cap-like headdress accompanied by a little panakawan-like figure, walks along a cobbled path through a beautiful landscape. The figures are carved in the simple style of East Javanese reliefs on Majapahit temples. The predominance of nature, in amazing detail, is unusual compared to other narrative temple reliefs. The exact provenance is difficult to determine. The artefacts are scattered in museums all over the world: the majority in Trowulan, as well as a large convolute in Jakarta, in Amsterdam, and elsewhere. Fixing the order of the panels is a challenge. This paper discusses two major topics: (A) presenting depictions of landscape and nature in visual art; (B) comparison with Old Javanese texts narrating journeys through landscape and nature. These exercises will provide some conclusions about the function of landscape and nature in the reliefs and their purpose at their original sites. Questions on provenance will also be raised, including the documentation practice of the colonial Dutch and Indonesian Archaeological Services. A number of the panels have been documented by the OD (Dutch Oudheidkundige Dienst), archived in OD photos entitled “Reliefs from Trowulan”, other panels have been documented as being from the site Menak Jinggo in Trowulan. In my paper, I call the reliefs under investigation the “Trowulan reliefs”. N.J. Krom’s (1923) suggestion of doing research on the convolute of these reliefs has never been undertaken, now 100 years later it is time to do so.